Better Association Between Q Angle and Patellar Alignment Among Less Displaced Patellae in Females with Patellofemoral Pain Syndrome: A Correlation Study with Axial Computed Tomography - Lin, Da-Hon; Lin, Chien-Ho Janice; Lin, Jiu-Jenq; Jan, Mei-Hwa; Cheng, Cheng-Kung; Lin, Yeong-Fwu (IntechOpen, 2012)
None